The Effect of Food Delivery Services on Restaurant Operations - Othman, Ibrahim; Mat Radzuan, Indera Syahrul; Shamsudin, Zarina; Ismon, Nur Yuhanis (Research in Management of Technology and Business, 2025)
This research investigates the effects of food delivery services on restaurant owners in Batu Pahat, Johor, Malaysia. The study aims to identify which independent variables, such as coercive pressure, mimetic pressure, normative pressure, and technology acceptance model, have the most significant impact on their behavioral intention to apply for food delivery services. Using a convenience sampling method, primary data was collected through self-administered surveys distributed via Google Forms across various digital platforms over three months. 180 respondents participated, providing insights into their preferences and priorities. The findings reveal that coercive, mimetic, normative, and technology acceptance models significantly influence behavioral intention to apply for food delivery services. In contrast, coercive pressure was found to have no significant effect. The study suggests further exploration into additional variables and the use of diverse sampling methods to enhance the reliability and generalizability of the results.